Repititive impact training: An integrated evaluation in competitive figure skaters. A multi-disciplinary approach - Lockwood, K. L. (1997)
The purpose of this thesis was to describe the effects of a history of repetitive impact load-type training on the biomechanical , physiological, bone mineral density, and biochemical profiles in competitive figure skaters. A multi disciplinary approach to research was used to conduct a series of six investigations. Chapter III describes two biomechanical analyses conducted to describe the impact nature of training in figure skating. The vertical impact forces absorbed by the skaters upon landing single, double, and triple revolution jumps were quantified. Results revealed that impact forces increased significantly with additional revolution and technical difficulty. The second kinematic analysis revealed that although, all landings of on-ice jumps are technically identical, the methods of impact absorption were significantly different. The physiological profiles of 55 competitive figure skaters were described in Chapter IV. Autobiographical questionnaires were analysed to quantify training time and intensity, injury histories, calcium intake, and maturity status. A linear relationship was observed between technical calibre, maturation, and physiological attributes. Projects described in Chapter V were conducted to examine the potential effects of impact load-type jump training on bone mineral density (BMD) profiles of the same skaters. These analyses revealed that skaters had significantly higher BMD measures at all sites examined. Furthermore, a sport specific comparison of the lower extremities revealed significantly higher BMD in the landing limb of all calibres of skaters. Chapter VI hypothesized that impact load-type training may induce an adaptive response in the developing skeleton which has the potential to be observed by measuring biochemical markers of bone turnover. Three of the six markers examined: osteocalcin, PICP, and ICTP showed significant differences between calibre of skaters. The results of this series of investigations provided insight into the significant relationships found between mechanical loading and physiological, BMD, and biochemical profiles of these athletes. These results may be used to develop guidelines for the sport of figure skating to safeguard the health of these young participants.